Musculoskeletal Symptoms in Patients With Cryopyrin‐Associated Periodic Syndromes: A Large Database Study. Issue 11 (November 2015) - Houx, Laetitia; Hachulla, Eric; Kone‐Paut, Isabelle; Quartier, Pierre; Touitou, Isabelle; Guennoc, Xavier; Grateau, Gilles; Hamidou, Mohamed; Neven, Bénédicte; Berthelot, Jean‐Marie; Lequerré, Thierry; Pillet, Pascal; et al.
Abstract : Objective: To determine the type and frequency of musculoskeletal symptoms at onset and during followup of cryopyrin‐associated periodic syndromes (CAPS). Methods: We retrospectively recorded the articular and muscular symptoms of patients with CAPS followed up in French hospitals. Data were presented as frequencies or the median (range), and patient groups were compared using chi‐square test, Fisher's exact test, and Mann‐Whitney test. Results: The study included 133 patients (33 children), 20 with familial cold autoinflammatory syndrome, 88 with Muckle‐Wells syndrome, 22 with chronic infantile neurologic, cutaneous, articular syndrome, and 3 with unclassified CAPS. The median age was 35 years (range 0–78 years) at the time of the study, 1 year (range 0–41 years) at symptom onset, and 23 years (range 0–58 years) at diagnosis. The disease was sporadic in 17% of the patients. Cutaneous symptoms predominated at onset (77%), followed by articular symptoms (30%). The p.Thr348Met and p.Arg260Trp NLRP3 mutations were significantly associated with the presence and absence of articular symptoms at onset, respectively. During followup, 86% of the patients had musculoskeletal symptoms, 88% had arthralgia, and 58% had arthritis, but only 9% had joint destruction. Tendinopathies occurred in 21.5% of the patients, tender points in 16.5%, and myalgia in 33%. Only 3 patients had typical knee deformities. Radiographs were rarely obtained. Except for bone deformities, osteoarticular symptoms occurred at similar frequencies in the different CAPS phenotypes. Conclusion: Joint manifestations were frequent in all CAPS phenotypes. Bone deformities were rare. Musculoskeletal manifestations varied within given families but tended to worsen over time.